Pathways of carbonate sediment accumulation in a large, shallow lake - Rostási, Ágnes; Rácz, Kornél; Fodor, Melinda A.; Topa, Boglárka; Molnár, Zsombor; Weiszburg, Tamás G.; Pósfai, Mihály (Frontiers in Earth Science, 2022)
Since carbonate formation is an important process linking inorganic and biological components of freshwater ecosystems, we characterized the formation of modern carbonate sediments in a large, shallow, calcareous lake (Lake Balaton in Hungary). We measured the amount of allochtonous mineral particles delivered to the lake by tributaries and through the atmosphere over a two-year period, and estimated the mass of carbonate minerals that precipitated from lakewater. Chemical and structural features of mineral particles from various sources were also studied. Both the mineralogical character and the amount of particles delivered by streams and through the atmosphere were similar, and formed a minor fraction of the annual sediment increment (~5–6 % by mass). Since the watercourses feeding the lake had high concentrations of Ca2+, Mg2+ and HCO3– (with a Mg/Ca mol ratio ranging from 1 to 4), Mg-bearing calcite (with 2 to 17 mol% MgCO3) was found to continually precipitate in the lake. According to X-ray powder diffraction measurements, the Mg content of calcite increased from West to East, in parallel with changes in water chemistry. Dolomite was detected as a minor phase, and in the eastern part of the lake it typically produced a split 104 peak in X-ray diffractograms, suggesting two distinct sources: stoichiometric dolomite was allochtonous, whereas a Ca-rich protodolomite fraction formed in the lake. Mg-bearing calcite precipitating in the lake was found by far the largest contributor to sediment formation, with an estimated annual accumulation of about 0.75–0.9 mm consolidated sediment; thus, ~89 % of the currently forming sediment consists of autochtonous carbonate. In addition to providing new estimates for the rates of accumulation of distinct sediment fractions, our results also provide a baseline for further studies on the retention and release of nutrients by sediment minerals.